2002
DOI: 10.1073/pnas.012032699
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of estrogen receptor β gene impairs spatial learning in female mice

Abstract: Here we provide the first evidence, to our knowledge, that estradiol (E 2) affects learning and memory via the newly discovered estrogen receptor ␤ (ER␤). In this study, ER␤ knockout (ER␤KO) and wild-type littermates were tested for spatial learning in the Morris water maze after ovariectomy, appropriate control treatment, or one of two physiological doses of E 2. Regardless of treatment, all wild-type females displayed significant learning. However, ER␤KOs given the low dose of E 2 were delayed in learning ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
137
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(149 citation statements)
references
References 72 publications
10
137
0
2
Order By: Relevance
“…However, it may be that activation of ERb with DPN resulted in a more consistent retention of this previously learned association than was produced by activation of ERa by PPT. Studies that have examined the role of ERs in estrogen's effects on learning and memory have suggested that the ERb subtype is important for learning and memory, including spatial learning (Rissman et al, 2002) and retention of spatial and inhibitory avoidance memory tasks (Rhodes and Frye, 2006). Conversely, activation of the ERa subtype may inhibit learning (Fugger et al, 2000).…”
Section: Possible Interpretations Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it may be that activation of ERb with DPN resulted in a more consistent retention of this previously learned association than was produced by activation of ERa by PPT. Studies that have examined the role of ERs in estrogen's effects on learning and memory have suggested that the ERb subtype is important for learning and memory, including spatial learning (Rissman et al, 2002) and retention of spatial and inhibitory avoidance memory tasks (Rhodes and Frye, 2006). Conversely, activation of the ERa subtype may inhibit learning (Fugger et al, 2000).…”
Section: Possible Interpretations Of the Resultsmentioning
confidence: 99%
“…Use of these techniques have helped to identify the involvement of ERa and/or ERb in several biological functions, including mating and reproduction (Ogawa et al, 1998(Ogawa et al, , 1999Hewitt and Korach, 2003), anxiety (Krezel et al, 2001;Walf and Frye, 2005;Imwalle et al, 2005;Lund et al, 2005), learning and memory (Fugger et al, 2000;Rissman et al, 2002), wheel running (Ogawa et al, 2003), and food intake (Geary et al, 2001;Roesch, 2006). For example, ERKO studies in mice have shown that ERa is required for normal sexual receptivity and fertility in mice and rats, whereas ERb does not appear to be critical for reproductive function (Hewitt and Korach, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E 2 may have actions in the hippocampus to improve learning via traditional ligand-dependent actions at intracellular ERs [19,20,42]. In support, E 2 administered to ERβ knockout mice does not enhance spatial learning compared to vehicle [73]. Further, there may be ER specific effects of E 2 to enhance learning.…”
Section: Discussionmentioning
confidence: 96%
“…In the same line, ERb knockout mice are unable to learn a spatial task (Rissman et al, 2002;Liu et al, 2008), while the administration of an agonist of these receptors, but not an ERa agonist, improves the performance of mice in hippocampus-dependent memory tasks (Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%